2009
DOI: 10.1007/s11481-009-9185-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cytokines as Biomarkers of Alcohol Abuse and Alcoholism

Abstract: There are currently no consistent objective biochemical markers of alcohol abuse and alcoholism. Development of reliable diagnostic biomarkers that permit accurate assessment of alcohol intake and patterns of drinking is of prime importance to treatment and research fields. Diagnostic biomarker development in other diseases has demonstrated the utility of both open, systems biology, screening for biomarkers and more rational focused efforts on specific biomolecules or families of biomolecules. Long term alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 74 publications
(74 reference statements)
4
129
3
1
Order By: Relevance
“…The association between SUD and an increased hsCRP level remained significant in men even after multiple adjustments, which is in line with previous findings regarding increased levels of inflammation markers in alcoholics (Achur et al, 2010) and subjects with cannabis abuse or dependence (Costello et al, 2013). In drinkers, the increased level of pro-inflammatory cytokines has been shown to be associated with chronic and acute alcoholinduced lever diseases, but also with a significant increase in spontaneous cytokine production (Achur et al, 2010).…”
Section: Sud and Inflammationsupporting
confidence: 89%
See 1 more Smart Citation
“…The association between SUD and an increased hsCRP level remained significant in men even after multiple adjustments, which is in line with previous findings regarding increased levels of inflammation markers in alcoholics (Achur et al, 2010) and subjects with cannabis abuse or dependence (Costello et al, 2013). In drinkers, the increased level of pro-inflammatory cytokines has been shown to be associated with chronic and acute alcoholinduced lever diseases, but also with a significant increase in spontaneous cytokine production (Achur et al, 2010).…”
Section: Sud and Inflammationsupporting
confidence: 89%
“…A longitudinal study found generalized anxiety disorder (GAD) to be associated with an increased CRP level, but this association was attributable to health-related factors such as BMI and medication use (Copeland et al, 2012). Concerning substance use disorders (SUD), our group previously reported an association between moderate alcohol consumption and lower levels of IL-6 and TNF-a (Marques-Vidal et al, 2012c), whereas a recent review concluded that the levels of pro-inflammatory cytokines are increased in patients suffering from chronic alcoholism (Achur et al, 2010). Among the very few studies that examined the role of other SUD, Costello et al (Costello et al, 2013) showed a prospective positive association between the CRP level and any substance abuse or dependence in the community and Nabati et al (Nabati et al, 2013) found some elevated cytokines in opium addicts (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies show correlation between low intake and low pro-inflammatory cytokines [2,25,114]. Our results reflect these findings for TNF and IL-1β but not IL-6, which had the opposite effect.…”
Section: Relationship Between Cytokine/crp Levels and Non-pain Factorssupporting
confidence: 88%
“…In human opiate addicts, the level of TNF-α expression in the brain (locus coeruleus) is higher than that in control subjects (Dyuizen and Lamash 2009). Levels of circulating TNF-α are altered in alcoholics, opiate addicts, and cocaine or marijuana abusers (Baldwin et al 1997;Peng et al 1999;Irwin et al 2007Irwin et al , 2009Gonzalez-Quintela et al 2008;Sacerdote et al 2008;Li et al 2009;Franchi et al 2010), and TNF-α may be a candidate biomarker of alcohol abuse and alcoholism (Achur et al 2010). In our study in animal, TNF-α (−/−) mice were more sensitive to METH self-administration and had a higher motivation for getting METH than wild-type mice.…”
Section: Discussionmentioning
confidence: 99%